Unusual manifestation of cutaneous toxoplasmosis in a HIV-positive patient - Fong, M.Y.; Wong, K.T.; Rohela, M.; Tan, L.H.; Adeeba, K.; Lee, Y.Y.; Lau, Y.L. (2010)
We report a case of unusual cutaneous toxoplasmosis manifestation in a HIV-positive patient. He presented with hard and painful nodular lesions on the arms, hands and chest. Serology tests for anti-Toxoplasma antibody were negative. However, histopathologic examination of the lesion revealed foci of macrophages containing crescent-shaped organisms resembling the zoites of the protozoan parasite Toxoplasma gondii. Ultrastructure examination under electron microscopy and PCR confirmed the organism as T. gondii.